The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/mcb.25.10.3875-3885.2005
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein Met30 Is Required for Multiple Steps in the Budding Yeast Cell Cycle

Abstract: The Saccharomyces cerevisiae ubiquitin ligase SCF Met30 is essential for cell cycle progression. To identify and characterize SCF Met30 -dependent cell cycle steps, we used temperature-sensitive met30 mutants in cell cycle synchrony experiments. These experiments revealed a requirement for Met30 during both G 1 /S transition and M phase, while progression through S phase was unaffected by loss of Met30 function. Expression of the G 1 -specific transcripts CLN1, CLN2, and CLB5 was very low in met30 mutants, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 51 publications
(66 reference statements)
0
45
0
Order By: Relevance
“…19 By comparison, previous reports using cells from human prostate cancer cell lines and Yoshida sarcoma their methionine stress-sensitive MDAMB468 parental cell line. The proliferation rate of both the MDAMB468 and the isolated R8 clone of resistant MDAMB468 cells in Met+ medium was similar, but only the resistant cells maintained the ability to proliferate in Met-Hcy+ medium ( Fig.…”
Section: S-adenosylmethionine Supplementation Suppresses Methionine Smentioning
confidence: 95%
See 2 more Smart Citations
“…19 By comparison, previous reports using cells from human prostate cancer cell lines and Yoshida sarcoma their methionine stress-sensitive MDAMB468 parental cell line. The proliferation rate of both the MDAMB468 and the isolated R8 clone of resistant MDAMB468 cells in Met+ medium was similar, but only the resistant cells maintained the ability to proliferate in Met-Hcy+ medium ( Fig.…”
Section: S-adenosylmethionine Supplementation Suppresses Methionine Smentioning
confidence: 95%
“…In the model system, yeast, a regulatory pathway connecting sulfur-containing metabolites, most notably methionine, with cell cycle regulation, has been suggested to respond primarily to S-adenosylmethionine (SAM) levels. [18][19][20] Furthermore, earlier studies showed that reducing SAM synthesis blocks proliferation of leukemic cells. 16,17 Therefore, we hypothesized that methionine dependence is a reflection of limiting SAM availability caused by reduced flux through the methionine metabolic pathway in Met-Hcy+ conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major function of this protein is to generate negative feedback by the deactivation of the Met4p through polyubiquitination, resulting in a down-regulation of S-adenosylmethionine, the major methyl donor in the cell, thus providing a strong oscillatory potential. The CMtr complex is conserved in eukaryotes and may constitute a more general redox state checkpoint in the chromosome cycle (30).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of SCF Met30 control of Met4 activity is clearly demonstrated by the finding that the lethality resulting from the inactivation of MET30, leading to unbridled Met4 activation function, can be bypassed by deletion of the activation domain of Met4 or the deletion of MET32, but not of CBF1, MET28, or MET31 Su et al 2005). Consistent with Met32 having an important role in MET gene expression, a truncated version of Met32 (Met32D145-192) acts as a dominant suppressor of met30 null mutations by interfering with the recruitment of Met4 to both Cbf1 and Met31/32-dependent promoters (Su et al 2008).…”
Section: Pathway Genesmentioning
confidence: 99%